(untitled) (Altre Modernità, 2012)
Based on Bachelard’s phenomenological take on the temporality of imagination, this paper analyzes a few works by Marcos Lutyens, a contemporary artist. Bachelard offers two concepts that bring about an altered temporality of material imagination: resonance and reverberation. Resonance is a dynamical condition through which the world discloses its imaginary opportunities: it oscillates with larger amplitude at some frequencies than it does at others. Under this intense state, the attunement of two rhythms, the rhythm of consciousness and the world-rhythm, can occur. Reverberation technically means a further step, i.e., a change in the configuration of our rhythmical settings through the intrusion of an alien vibration: we are possessed by external rhythms; the so-called depth of our interiority is affected by an alien energy, and we vibrate in tune with alien rhythms. By reshaping the rhythmical organization of one’s perception (using hypnosis, a trance state and registered body automatisms), Lutyens tries to trace pathways related to unconscious thought processes. Shifting the experience of duration, he moves through imaginary environments within the preconscious that are progressively charted and recorded. Consequently it appears that what is “penetration” in space is marked by resonance and reverberation in time.